(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Wide introduction of modern information and communication technologies in education leads to informatization of all fields of science, intellectualization of educational activities, deepening of integration processes, improvement of educational system infrastructure and its management mechanisms.